NEW DATA ON VINCENTITE - Tarkian M.; Klaska K.-H.; Stumpfl E.F. (My University, 2002)
Vincentite was described in 1974 as a new palladium-bearing mineral species in platinum-gold concentrates from the Riam Kanan River, southeastern Borneo. Because of its small grain-size, it was not possible at that time to obtain satisfactory X-ra y data. The mineral has now been re-investigated. In reflected light, it is light brownish grey; pleochroism and anisotropy are w eak. Maximum and minimum values of reflectance in air for standard wavelengths (470, 546, 589 and 650 nm) are: 38.8/43.1; 45.4/ 51.3; 48.0/54.2 and 50.8/55.9, respectively. New electron-microprobe analyses confirm the formula (Pd,Pt) 3(As,Sb,Te) attributed earlier. The X-ray powder-diffraction patterns obtained with a microdiffractometer were indexed on a monoclinic cell with a 11.226(3), b 6.318(2), c 8.047(2) Å, 100.95(4)°, V 560.4(2) Å3; a:b:c = 1.776:1:1.273. For Z = 8, the calculated density is 10.86 g/cm3. The strongest five lines in the X-ray pattern ( d in Å(I)(hkl)) are: 1.800(10)(¯ 602), 1.775(9)(¯ 404), 1.758(8)(¯ 423), 1.745(8)(331) and 1.838(6)(600).
Keywords: vincentite; Pd mineral; new data; spectral reflectance; X-ray-diffraction pattern; unit-cell parameters